Pengaruh Harga dan Brand Awareness terhadap Keputusan Pembelian pada Konsumen Air Minum Kemasan Merek Boneva di PT. Davincy Airindo Kota Gorontalo - Antoni, Elpina Y.; Taan, Hapsawati; Juanna, Andi (SENTRI: Jurnal Riset Ilmiah, 2025)
The aim of this study is to determine (1) the influence of price on purchasing decisions for Boneva brand bottled drinking water products; (2) the influence of brand awareness on purchasing decisions for Boneva brand bottled drinking water products; and (3) the influence of price and brand awareness on purchasing decisions for Boneva brand bottled drinking water. The study used a quantitative approach with independent variables of price (X1) and brand awareness (X2), and dependent variable of purchasing decisions (Y). The population in the study were all consumers of Boneva brand drinking water in Gorontalo City with a sample of 100 respondents obtained through purposive sampling technique. Data analysis used multiple linear regression, partial test (t test), and simultaneous test (F test) with the help of SPSS. The results of the study show that (1) partially price has a positive and significant effect on purchasing decisions with a significant value of 0.002 < 0.05 and Thitung 3.150 > Ttable 1.984 (2) partially brand awareness has a positive and significant effect on purchasing decisions with a significant value of 0.001 < 0.05 and Thitung 2.603 > Ttable 1.984 (3) Simultaneously, the price and brand awareness variables have a significant influence on purchasing decisions with a significance value of 0.001 < 0.05 and Fcount 68.239 > Ftable 3.09. With an adjusted R Square value of 0.576  which means that 5.76 % of variations or changes in purchasing decisions can be explained by price and brand awareness variables, while the remaining 42.4 % are influenced by other factors not examined in this study.